Robust Audio Watermarking Algorithm - Asatryan, David G.; Tairyan, Sergej V. (Mathematical Problems of Computer Science, 2021)
In this paper, we propose an adaptive digital audio watermarking algorithm. The algorithm uses the local properties of an audiosignal to satisfy the properties of human auditory system. The efficiency and robustness of proposed algorithm is illustrated by examples of random attacks with various intensities and compression attacks in the spectrum domain.